Leafhopper genus Pediopsoides Matsumura (Hemiptera: Cicadellidae: Macropsinae), with descriptions of two new species from China - Yang, Liyuan; Zhang, Yalin (Zootaxa, 2013)
Two new macropsine species, Pediopsoides (Celopsis) montaninversa and P. (Pediopsoides) anchorides spp. nov. are described and illustrated from China. A key to distinguish males of Chinese species in this genus is provided, along with a checklist of the known species worldwide.